SYSTEMATICS, MORPHOLOGY AND DISTRIBUTION AREA OF HERPETOFAUNA (REPTILIA) OF CHELONIA AND SERPENTES REGION RECORDED IN CENTRAL FERGANA REGION (Scientific journal of the Fergana State University, 2024)
The purpose of the study is to study the diversity of the herpetofauna of Central Ferghana and to analyze the area of distribution in a cross-section of regions. The article presents the results of observations and research conducted in september-october 2023 in the Yazyavan region of Fergana region in order to study the herpetofauna of Central Fergana. Our observation studies were conducted in "Yozyovon Nature Monument", Yangiabad deserts and residential areas. We inform you that 10 species belonging to 7 families and 7 genera were identified as a result of the research: Tortoises - 1 species belonging to the family Chelonia: Central Asian tortoise (Testudo horsfieldi Gray, 1844); 3 species belonging to the subfamily of snakes (Serpentes): dice snake (Natrix tesellata Laurenti, 1768.), sand racer (Psammophis lineolatum Brandt, 1838.) and tatar sand boa (Eryx tataricus Lichtenstein, 1823.) ;The systematic position of the identified species was compared with the data of identifiers, international databases and the results of herpetofaunistic observations of other researchers. The morphology of the species was studied and morphological characters were presented. A list of species recorded in the area was compiled and coordinates were obtained (40.69N, 71.47E). The distribution coordinates of the species in Uzbekistan were studied and the preliminary conclusions about their distribution area were presented. The obtained results make it possible to form ideas about the diversity of reptiles and their distribution area.